Cross-Border Bank Mergers: What Lures the Rare Animal? - Gayle L. DeLong; Claudia M. Buch (Kiel Institute of World Economics (IfW), 2001)
Although domestic mergers and acquisitions (M&As) in the financial services industry have increased steadily over the past two decades, international M&As were relatively rare until recently. This paper uses a novel dataset of over 2,300 mergers that took place between 1978 and 2001 to analyse the determinants of international bank mergers. We test the extent to which information costs and regulations hold back merger activity. Our results suggest that banks operating in more regulated environments are less likely to be the targets of international bank mergers. Hence, the lifting of regulations can spur growth in cross-border bank mergers. Also, mergers tend to be less frequent if information costs are high.
Keywords: G21; F21; 330; cross-border banking; information costs; regulations; mergers and acquisitions; Bank; Internationale Bank; Fusion; Übernahme; Informationskosten; Bankenpolitik; Schätzung; Welt; Distanz